2009
DOI: 10.1371/journal.pgen.1000626
|View full text |Cite
|
Sign up to set email alerts
|

The Fission Yeast Homeodomain Protein Yox1p Binds to MBF and Confines MBF-Dependent Cell-Cycle Transcription to G1-S via Negative Feedback

Abstract: The regulation of the G1- to S-phase transition is critical for cell-cycle progression. This transition is driven by a transient transcriptional wave regulated by transcription factor complexes termed MBF/SBF in yeast and E2F-DP in mammals. Here we apply genomic, genetic, and biochemical approaches to show that the Yox1p homeodomain protein of fission yeast plays a critical role in confining MBF-dependent transcription to the G1/S transition of the cell cycle. The yox1 gene is an MBF target, and Yox1p accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 61 publications
6
67
0
1
Order By: Relevance
“…These results were not predicted by the observations that Nrm1 is unable to bind the Cdc10-C4 mutant protein and that Yox1 binding to MBFregulated promoters is Nrm1-dependent. 12,23 Hence, in addition to confirming the key role of Yox1 in the regulation of MBFdependent gene expression, our data suggests that Yox1 can function independently of Nrm1 to inhibit MBF activity.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…These results were not predicted by the observations that Nrm1 is unable to bind the Cdc10-C4 mutant protein and that Yox1 binding to MBFregulated promoters is Nrm1-dependent. 12,23 Hence, in addition to confirming the key role of Yox1 in the regulation of MBFdependent gene expression, our data suggests that Yox1 can function independently of Nrm1 to inhibit MBF activity.…”
Section: Resultssupporting
confidence: 77%
“…Previous work established that Yox1 and Nrm1 act as repressors of MBFdependent gene expression in S. pombe 12,13 and, moreover, several lines of evidence suggested that Yox1 and Nrm1 may act in the same pathway. 12 It has also been shown that MBF-dependent gene expression is specifically derepressed at the permissive temperature (25°C) in cells containing the temperature sensitive cdc10-C4 allele, which encodes a C-terminal truncation of the MBF component Cdc10, and moreover that MBF-dependent gene expression decreases when these mutant cells are placed at the non-permissive temperature (>32°C). 9,24 Interestingly, Nrm1 is unable to bind the mutant Cdc10 protein, suggesting that the derepression of MBF-regulated genes at the permissive temperature is due to the inability of mutant Cdc10 to bind Nrm1.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations